MULTIPLIKASI MERISTEM UBIKAYU (Manihot esculenta) DALAM MEDIA MURASHIGE AND SKOOG (MS) MODIFIKASI NAA (Naphthalene Acetic Acid) DAN BA (Benzyl Adenine) - Natalia Tinoncy Waro; Astutik Astutik; Astri Sumiati (Universitas Tribhuwana Tunggadewi, 2020)
This research aimed to see the effect of the addition of NAA and BA into MS media for the development of cassava micropropagation, furthermore, the composition of the media was appropriate to produce the maximum number of cassava shoots. The study was conducted using a completely randomized factorial design consisting of 2 factors, namely: Factor I: the concentration of Naphthalene Acetic Acid (NAA) consisted of 2 levels, namely: 0 mg / l (N0) and 0.1 mg / l (N1). The second factor was the concentration of Benzyl Adenine (BA) consisting of 4 levels: 1.0 mg / l (B1); 3.0 mg / l (B2); 5.0 mg / l (B3) and 7.0 mg / l (B4). Apply 8 treatment combinations, N0B1; N0B2; N0B3, N0B4, N1B1; N1B2; N1B3; N1B4. Observations were made on the variables: time of shoot initiation, number of shoots, number of leaves, and percentage of live and contaminated explants until the age of 16 weeks after sub-culture. The results showed that there was no interaction between the addition of the auxin hormone NAA and the cytokinin BA into MS medium at the time of shoot initiation, but both hormones could support the number of new shoots and the number of leaves per plantlet. Media without the addition of NAA with the addition of BA 1.0 - 3.0 mg / l was able to initiate new shoots the fastest, namely 7-10 days. The best number of shoots of cassava (4.43 shoots/explant) used MS medium without the addition of NAA with BA 3.0 mg / l for 16 weeks (4 months) of culture.